What is the optimal classical style sub-technique during uphill roller skiing in elite male cross-country skiers? - Lund-Hansen, M.; Gløersen, Ø.; Rud, B.; Losnegard, T. (European Journal of Applied Physiology, 2023)
Purpose To compare performance, physiological and biomechanical responses between double poling (DP) and diagonal stride (DIA) during treadmill roller skiing in elite male cross-country skiers.